Causes of the Extreme Hot Event on February 9, 2020, in Seymour Island, Antarctic Peninsula - Bae, Hyo-Jun; Kim, Seong-Joong; Kim, Baek-Min; Kwon, Hataek (Frontiers in Environmental Science, 2022)
On early February of 2020, two consecutive extreme warming events of three day interval at the similar location occurred over the Antarctic Peninsula (AP). The later event, that occurred on February 9, 2020, exhibited a second-hightest temperature record of 15.5°C at Marambio station, located on Seymour Island, northeast of the AP. To understand the possible cause of the extreme warming event, we analyzed extreme warming events that occurred on Seymour Island during February over the past 40 years by using observational data from Marambio station alongside the European Center for Medium-Range Weather Forecasts Reanalysis v5 (ERA5) data. The results revealed that the extreme warming event on February 9, 2020 occurred due to the foehn and large-scale horizontal advection. In foehn winds, radiative heating and isentropic drawdown occur simultaneously. The horizontal advection of heat, which leads to extreme warming events, is associated with the strong blocking high in the upper and lower atmosphere. Contrary to the average characteristics of extreme warming events in February over the past 40 years, the extreme warming on February 9, 2020, occurred not only in the AP but also throughout entire West Antarctica.